ความสัมพันธ์ระหว่างความฉลาดทางอารมณ์ สภาพแวดล้อมในหน่วยงาน กับประสิทธิผลของงานของพยาบาลวิชาชีพงานการพยาบาลผ่าตัด โรงพยาบาลศูนย์ - สุมาลัย ประจวบอารีย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
To study the level of emotional quotient, workplace environment, job effectiveness and to identify the relationships between emotional quotient, workplace environment, and job effectiveness of professional nurses of perioperative nursing service, Regional Hospital and Medical Centers. Subjects were 249 professional nurses of perioperative nursing who were selected by multi-stage sampling technique. The research instrument were emotional quotient screening test, questionnaires of workplace environment and job effectiveness. The content validity were established and reliability were .87 and .94 respectively. Data were analyzed by percentage, mean, standard deviation and Pearson s product moment correlation. Research findings were as follows : 1.Job effectiveness and workplace environment of professional nurses of perioperative nursing service Regional Hospital and Medical Centers were at good level. (X = 4.17 and 4.01 respectively). 2. Emotional quotient of professional nurses of perioperative nursing service Regional Hospital and Medical Centers was at normal level. (X = 165.99). 3. Emotional quotient was positive significantly correlated with job effectiveness of professional nurses of perioperative nursing service at the .05 level (r = .45). 4. Workplace environment was positive significantly correlated with job effectiveness of professional nurses of perioperative nursing service at the .05 level (r = .71).